Bone-Patellar Tendon-Bone Allograft Preparation Technique for Anterior Cruciate Ligament Reconstruction - Sachin Allahabadi MD; Thomas W. Fenn BS; Jordan H. Larson BS; Shane J. Nho MD, MS (SAGE Publishing, 2023)
Background: Allograft anterior cruciate ligament (ACL) reconstruction, while it may have a higher failure rate in younger and more active populations, continues to serve as a viable graft option for the appropriately indicated patient. Efficient bone-patellar tendon-bone (BTB) allograft preparation is beneficial to reduce operating time and ensure optimal reconstruction with bony fixation. Indications: ACL reconstruction with BTB allograft is indicated for skeletally mature and older patients, patients who are less active and have fewer physical demands, patients who have had previously harvested autograft, circumstances where an autograft harvest is inadequate, patients with multiligament knee injuries, and patients who prefer allograft use. Technique Description: The central third of the BTB allograft is harvested, aiming for a graft diameter of 10 mm along the tendon. The tibial bone plug is first cut to a length of 25 to 30 mm and width of 10 mm with the saw at a 70° angle to the bone. The patellar bone plug is cut to a length of 25 mm and width of 10 mm with the saw at a 45° angle to the bone. The bone plugs are mobilized, and soft tissue is dissected to free the graft. The graft is trimmed until it fits through a 10-mm sizer on each side. A single hole is created with a k-wire in the patellar bone plug, and a #5 Ethibond suture is passed. On the tibial bone plug, 2 holes are made perpendicular to one another, and a #2 Fiberwire suture is passed through each of these holes. These sutures allow for facilitated graft passage and tensioning. Once the graft is affixed with interference screws, the graft is arthroscopically evaluated throughout range of motion. Results: ACL reconstruction with BTB allograft provides high success rates in appropriately selected patients. Data demonstrate more optimal mechanical properties by harvesting the central third of the allograft tendon in younger donors. Non-irradiated and less chemically processed grafts are also preferred to optimize biomechanical properties. Discussion/Conclusion: Bone-patellar tendon-bone allograft with 2 bone plugs offers a reliable alternative to other allografts or autografts. Preparing the allograft in a fashion similar to an autograft harvest may increase familiarity with techniques and facilitate surgical efficiency and graft passage. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.